Erosividad de las precipitaciones en Tandil, provincia de Buenos Aires - Di Leo, C. M. (1999)
The objective of this paper was to evaluate the utility of a short period pluviografic data for the estimation of the monthly and annual erosivity in Dique Seco, Tandil, Buenos Aires, Argentina. The methodology used by the Universal Soil Loss Equation (USLE) for calculation of the R factor was applied to a 1972-1977 serie, and the results compared with other published data. A close relationship between the product of the total volume of a storm by the maximum intensity in 30 minutes and the R factor was confirmed. The coefficients of adjustment Bi was applied. A higher rain erosivity was confirmed for the spring and summer months.